Buddhist Ethics and Corporate Culture of Nepalese Higher Education Institutions in Kathmandu Valley - Shrestha, Narendra Kumar (Prajñā Journal of Buddhist Studies, 2026)
This study aims to examine the impact of Buddhist ethics, as interlaced with the Four Noble Truths, Five Precepts, Four Divine Emotions and Ten Perfections of Buddhism, under the mediating role of the Eightfold Paths, on the corporate culture of selected Nepalese higher education institutions affiliated with five Nepalese universities and located in the Kathmandu Valley. Using an explanatory research design and purposive sampling, the study collected data from 404 employees of these institutions via a structured, closed-ended questionnaire. The correlation and regression analyses indicate a significant impact of Buddhist ethical factors on corporate culture and a positive relationship between the Buddhist Eightfold Path and corporate culture in these institutions. Thus, it can be concluded that the organizational values and culture in Nepalese higher education institutions can be enhanced by teaching Buddhist ethical norms, values and principles. The study aims to provide explicit insight into how an indigenous ethical model can stimulate institutional development and offer practical guidance for educational leaders and administrators seeking culturally integrated approaches to managing Nepalese higher education institutions.